Tungsten Argon Arc Welding Crack Analysis and Numerical Simulat ion for Residual Stress of Co-Based Superalloy - Zhongyao Li; Li Feng; Jianjun Guan; Yan Zhao; Yanhong Yang; Jiaojiao Zhu (Archives of Metallurgy and Materials)
The influence of welding current decay time on the repair of Co-based superalloy by tungsten argon arc welding spot welding are investigated by means of simulation and experiments. The results show that: the maximum tensile stress of residual stress after welding is distributed in the center area, gradually decreases towards the edge area, and mainly exists in the form of compressive stress in the edge area. On the same welding current, with the increase of attenuation time, the overall trend of temperature and stress distribution, and the stress value increases. The larger the fusion zone (FZ) crack area and the smaller intergranular cracks in the heat affected zone (HAZ) decrease. Currently, there is limited research on the influence of welding current decay time on the repair of Co-based superalloys via tungsten argon arc spot welding.